(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article deals with an analytic assessment of scientific works devoted to a particular of the topical studies in cognitive and cultural linguistics, the concept of "wealth" that is included in the corpus of core ideas of various systematic languages. The article is composed of the systematization of the majority of known scientific results of verbal representation, as well as the structuring of the idea of "wealth" in the context of English and Uzbek languages.